2018
DOI: 10.1093/biolinnean/bly073
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of a patchily distributed philopatric migrant: implications for management and conservation

Abstract: Significant demographic fluctuations can have major genetic consequences in wild populations. The lesser kestrel (Falco naumanni) has suffered both population declines and range fragmentation during the second half of the 20 th century. In this study we analysed multilocus microsatellite data to assess the genetic structure of the species. Our analysis revealed significant genetic structuring of lesser kestrel populations, not only at the cross-continental scale, but also regionally within the Central and East… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Several studies have suggested that reintroduction campaigns mitigated losses of genetic diversity in the regions in which they occurred (Brown et al, ; Johnson et al, ; Ponnikas, Ollila, & Kvist, ). However, studies comparing reintroduced populations to naturally recovered populations, which may retain high heterozygosity (Bounas et al, ), are lacking, as are studies assessing potential losses in local and locally adaptive genetic diversity among reintroduced and naturally recovered populations. As the legacy of falcon conservation continues to guide similar contemporary reintroduction and management programs (Carroll et al, ; Watson, ), such studies will help inform ongoing conservation efforts for other species.…”
Section: Anthropogenic Impacts On the Falcon Genome And Research Oppomentioning
confidence: 99%
“…Several studies have suggested that reintroduction campaigns mitigated losses of genetic diversity in the regions in which they occurred (Brown et al, ; Johnson et al, ; Ponnikas, Ollila, & Kvist, ). However, studies comparing reintroduced populations to naturally recovered populations, which may retain high heterozygosity (Bounas et al, ), are lacking, as are studies assessing potential losses in local and locally adaptive genetic diversity among reintroduced and naturally recovered populations. As the legacy of falcon conservation continues to guide similar contemporary reintroduction and management programs (Carroll et al, ; Watson, ), such studies will help inform ongoing conservation efforts for other species.…”
Section: Anthropogenic Impacts On the Falcon Genome And Research Oppomentioning
confidence: 99%
“…The indirect evidence of limited gene flow found in our study, could be also a result of the interaction between philopatry, territoriality and the lack of suitable habitat for populations of ground-sparrows in an urban setting. Philopatry and territoriality keep individuals within a population, thereby decreasing gene flow and increasing genetic differentiation between populations (Bounas et al, 2018;Rodríguez-Bardía et al, 2022). In urbanized sites ground-sparrow males may increase their territories to search for additional food sources (Juárez et al, 2020).…”
Section: Geneticsmentioning
confidence: 99%